The material text in Wycliffite biblical scholarship inscription and sacred truth - Lavinsky, David (Woodbridge Boydell & Brewer Ltd., 2017)
The reform movement known variously as Wycliffism or Lollardy is now a familiar feature of the premodern intellectual and religious landscape. but even though "heresy" has migrated to the forefront of medieval studies in recent decades. Wycliffite biblical scholarship itself has escaped sustained attention, especially its different tiers of textual form and practice. This book examines Wycliffism as it moves from late scholastic discourses of academic biblical study to the material contexts of English book and manuscript production; it also considers changing notions of biblical materiality itself. Such a concern is not limited to the empirical analysis of the book-object itself, but extends to scripture's material forms and identities as they were imagined, theorized, and made the subject of far-reaching speculation in textual criticism and hermeneutics. In addition to Wycliff's academic writing, the book also addresses the movement's most significant textual assemblages in a major contribution to reframing our understanding of a key moment in English religious and cultural history
Introduction -- "De Pellibus Bestiarum": scripture, realism, and material form -- "Stories of Þe elde testament": adherence, supersession, and the "proces" of reading -- "We speke not of enke and parchemyn": voice, form, and textual supplement -- Rolle's "blessyd boke": heresy, interpolation, and the material text -- The "sentence of olde holy doctouris": Gospel commentary and the materialities of the literal sense -- Conclusion
Keywords: Wycliffe, John -- -1384 -- Influence; Reformation; Lollards; Christian Heresies; Christian Heresies; Lollards; Reformation; Wycliffe, John -1384